2017
DOI: 10.1149/2.1531712jes
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Micro Copper Walls by Localized Electrochemical Deposition through the Layer by Layer Movement of a Micro Anode

Abstract: The process of localized electrochemical deposition (LECD) offers the potential to fabricate complex structures using the layer-bylayer movement of an anode or a cathode, similar to 3D printing. This work demonstrates the fabrication of micro sized copper walls using the LECD process, which is critical for MEMS and semiconductor-related applications. First, copper walls with different morphologies were deposited by moving the micro anode layer by layer and controlling the applied voltage between the electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…[9][10][11][12] In addition, by using the MAGE technique, various shapes and complicated geometries can be fabricated by moving the tip of the microanode to form the required track, such as copper walls, helical structures, etc. [13][14][15] Significant research effort has been devoted to investigating and improving the LECD technique. Yeo et al reported that ultrasonic vibrations can be used to increase mass transport at a localized region leading to a high rate of deposition; this improves the concentricity and increases the porosity of the fabricated columns.…”
mentioning
confidence: 99%
“…[9][10][11][12] In addition, by using the MAGE technique, various shapes and complicated geometries can be fabricated by moving the tip of the microanode to form the required track, such as copper walls, helical structures, etc. [13][14][15] Significant research effort has been devoted to investigating and improving the LECD technique. Yeo et al reported that ultrasonic vibrations can be used to increase mass transport at a localized region leading to a high rate of deposition; this improves the concentricity and increases the porosity of the fabricated columns.…”
mentioning
confidence: 99%
“…However, most of the aforementioned studies have focused on column deposition [30] and the production of extended structures [31]. In 2000, Johansson et al used LECD to prepare a nickel column and deposited a portal made by bridging two separately built structures [32], but the joining structure was not fully formed.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the conformational design complexity of threedimensional (3D) microproducts, Ciou et al combined the LECD process with a real-time 3D image feedback distance control system and fabricated two types of 3D microstructures: helical springs with a low pitch angle and inverted tripods [16]. Wang et al used a novel LECD system by moving the micro anode layer-by-layer and controlling the applied voltage between the electrodes to fabricate copper walls [17].…”
Section: Introductionmentioning
confidence: 99%